Inpatient Medicare TKA Patients Have Distinct Characteristics and Worse Outcomes: Implications for the New CMS PROMs Policy - Elmenawi, Khaled A.; Pasqualini, Ignacio; Jevnikar, Benjamin E.; Emara, Ahmed K.; Zhang, Chao; Piuzzi, Nicolas S.; Cleveland Clinic Adult Reconstruction Research (CCARR) Group (The Journal of Knee Surgery, 2025)
The Centers for Medicare and Medicaid Services (CMS) recently mandated the collection of Patient-Reported Outcome-Based Performance Measures (PRO-PMs) for Medicare patients undergoing inpatient total knee arthroplasty (TKA). The policy's generalizability remains a concern. Therefore, we aimed to compare PROMs capture rates, patients' characteristics, and achieving the substantial clinical benefit (SCB) threshold between inpatient and outpatient Medicare TKA. A prospective cohort of Medicare patients aged ≥ 65 who underwent primary TKA between 2016 and 2022 at a single health system was analyzed (n = 7,926). Patients were categorized as inpatient (length of stay [LOS] > 24 hours, n = 2,812) or outpatient (LOS ≤ 24 hours, n = 5,114). Capture rates of CMS-mandated variables, baseline characteristics, and 1-year outcomes were compared. SCB was defined as a 20-point improvement in the Knee Injury and Osteoarthritis Outcome Score for Joint Replacement (KOOS-JR) per CMS criteria. Baseline capture rates were similar between groups (approximately 82.8%), but 1-year KOOS-JR completion was lower for inpatients (53.3% vs. 62.4%). Inpatients had higher comorbidity burden (CCI ≥ 2: 40% vs. 33%, p < 0.001), worse KOOS-JR (median 44.9 vs. 47.5, p < 0.001), lower VR-12 MCS scores (50.2 vs. 54.1, p < 0.001), and more frequent nonoperative joint pain (75.1% vs. 68.6%, p < 0.001) and back pain (67.4% vs. 63.8%, p < 0.001). Outpatients trended toward better SCB achievement (OR: 0.89, 95% CI: 0.78–1.00, p = 0.054). Compared to outpatients, inpatient Medicare TKA patients had lower 1-year PROM capture rates, more comorbidities, and worse baseline PROMs, with a trend toward not meeting CMS SCB thresholds. These differences highlight limitations in using inpatient-only data to assess national TKA outcomes, especially as outpatient procedures grow. Nonetheless, future studies with higher power should validate these findings. The level of evidence is III (retrospective).
Keywords: Medicare; total knee replacement; PROM